Chemostratigraphic Investigation of Early Carboniferous Tuffs and Limestones from the Irish Midlands Based on Geochemical and Geochronological Fingerprinting - Koch, Hilde Anna (Trinity College Dublin. School of Natural Sciences. Discipline of Geology, 2021)
The timing of mineralisation of the Irish Zn-Pb ore field is currently poorly understood. It can be improved by more accurate stratigraphic correlations of the Carboniferous (Mississippian Subsystem) host rocks (Heckel and Clayton, 2006; Richards, 2013). The position of altered volcanic ash layers in relation to the carbonate-hosted Zn-Pb deposits of Ireland makes them key potential isochronous marker horizons and thus provide possibilities to supplement the relatively coarse biostratigraphic resolution for these rocks. The purpose of this study is to establish a geochemical tephrostratigraphy for the Irish Midlands, which will refine the regional Mississippian stratigraphy and its relationship to the timing of mineralisation of Irish Zn-Pb deposits. Special emphasis is placed on the use of high-precision trace element geochemistry to test whether small, but significant, differences in bulk tuff chemistry can survive alteration and be used as a correlation tool. However, the study undertakes a multi-proxy approach, integrating bulk-rock geochemistry with apatite high-precision trace element and U-Pb zircon age data. The sampling is regional, and was undertaken in active (Navan) and abandoned (Lisheen and Rapla) mines or prospects (Stonepark and Slievedart) across the Irish Midlands. Seventy-nine tuff samples were powdered and chemically analysed for 51 trace elements, using high-precision solution quadrupole ICP-MS. Only 18 and 14 of the mineralogically separated samples contained zircon and apatite grains, respectively. Available grains were dated by U-Pb LA-ICP-MS. Apatite grains were analysed for 23 trace element abundances and for U-Pb ages to ensure they represented Early Carboniferous phenocrysts. Six different discrete eruptions or eruption sequences, which led to the deposition of volcanic ashes in the Irish Midlands, are identified using whole-rock Ti, Nb, Y, Al, Hf, Ta, La, Pr, Sm, Gd, Dy, Er, Yb concentrations in the modified matchogram approach of Marx et al. (2005). Each of the tuff layers in Navan, the Rathdowney Trend and Slievedart also exhibit unique and reproducible trends in REE+Y diagrams and share a similar parental magma composition. These results are supported by apatite trace element and U-Pb zircon age data, which have a supposedly more robust tephrochronological potential (Sell and Samson, 2011a; Harvey, 2014; Nicklen et al., 2015). Thus, the combination of the matchogram and bulk-rock trace element fingerprinting is a viable basis for the tuff identification and correlation as geochemical differences are significant enough to cause compositional separation. Importantly, alteration effects or mineralisation do not seem to preclude the use of selected bulk-rock trace element data as a chemostratigraphic tool. Although samples from the Stonepark area show contradictory results in bulk-rock vs apatite trace element data, the newly developed multi-proxy approach can be ideally applied to similar geological settings worldwide, to resolve stratigraphic relationships. All tuff samples from Navan, the Rathdowney Trend and nine out of eleven samples from Slievedart indicate an evolved magma composition. The volcanic centre for the evolved ashes is most likely in Ireland. However, the Limerick volcanic region is a possible source area for two sand-grade tuffs from Slievedart (samples Slievedart_3471/4_HK 237 and Slievedart_3470/15 _HK 238), which have an intermediate magma composition. U-Pb zircon ages, ranging from 350 Ma to 345 Ma, show that tuff samples were deposited in the Tournaisian and Early Viséan. This work also suggests, that the Tournaisian-Viséan boundary in Slievedart should be moved close to the tuffs in the Kilbryan Limestone Formation. Furthermore, this study supports the time- equivalence of the New Thin Bedded Unit in Tara Deep and the Tober Colleen Formation in Navan West. The Slievedart tuffs show that they are influenced by mineralisation, which implies an epigenetic origin of the sediment-hosted mineralisation of the underlying Zn-Pb deposit, which took place later than 347 Ma, which is the minimum age of dated ashes, while the timing of mineralisation in the other three study sites remains unclear. The possibility of utilising Sr isotope stratigraphy and trace element patterns as a secondary chemostratigraphic tool depends on available geomaterials. Brachiopods from Irish Mississippian limestones proved to be most suitable. Furthermore, the newly introduced in situ sampling technique employs the laser ablation unit as a milling device. Ahead of laser micro- sampling, potential sampling targets are mapped by LA-ICP-MS for their trace element distributions. Sampled material will be subsequently analysed using a quadrupole ICP-MS. This approach will improve Sr isotope data as it provides high-spatial resolution sampling (down to 2 x 2 μm) of clean fossil material, devoid of the surrounding matrix and alteration.
APPROVED
Keywords: Fingerprinting; altered volcanic ash; tuff; bulk-rock trace elements; geochronology; U-Pb zircon dating; apatite trace elements; Sr isotopes; in situ sampling; new sampling technique